ANALISIS FAKTOR-FAKTOR ENGAGEMENT DOKTER SPESIALIS DI RUMAH SAKIT JIWA PROF. DR. SOEROJO MAGELANG - Rina Kusumawati (Jurnal Admmirasi, 2021)
Background: One of the efforts to approach the hospital in specialist doctor management uses the concept of engagement, which is currently a new thing. Engagement is a predictor of organizational success, in this case the hospital, while specialist doctors are the key factor in the hospital organizational system that has the potential, both the potential for excellent performance and the potential for being unproductive. Purpose: To identify and describe the relationship between specialist doctors and hospitals engagement. Methods: This study uses a case study qualitative research type, to determine the phenomena in the context of life using a single case design holistic single case design. A single case study is used because this research is a very important case (critical case) to prove that case management at Prof. Dr. SOEROJO Magelang Mental Hospital. is held effectively and efficiently using a holistic design (single unit of analysis). Results: From the results of the data analysis, the research respondents stated that social support factors / professional resources, in this case related to the relationship with colleagues, superiors and the work environment had the highest influence on the engagement of specialist doctors with organizations / hospitals, namely 11.08%, then followed. by self-esteem or 9.72% self-esteem, then self-efficacy or 7.88%, then performance feedback is the lowest 7.19%. Conclusion: The underlying factors according to the nine specialist doctors who were research respondents that included in the job resources which were resources related to the hospital, co-workers, superiors and the work environment, the relationship between specialist doctors and hospitals at Prof. Dr. Soerojo Magelang Mental Hospital is social support, self esteem, self efficacy and performance feed back